2022
DOI: 10.3390/s22155781
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Pavement Defect Detection and Classification Using RGB-Thermal Images Based on Hierarchical Residual Attention Network

Abstract: A convolutional neural network based on an improved residual structure is proposed to implement a lightweight classification model for the recognition of complex pavement conditions, which uses RGB-thermal as input and embeds an attention module to adjust the spatial, as well as channel, information of the images. The best prediction accuracy of the proposed model is 98.88%, while the RGB-thermal is used as input and an attention mechanism is used. The attention mechanism increases the attention to detail of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…The results showed that the proposed method outperformed the intensity feature registration approach. The benefits of combining infrared and visible images for the interpretation of infrastructure defects were also reported on previous studies [15,59,60], highlighting the concept that the different targeted defects have enhanced texture and color characteristics registered in visible images, while the thermal data register important temperature differences related to faulty materials or components.…”
Section: Texture-based Segmentation For Improving Multi-modal Analysi...supporting
confidence: 65%
“…The results showed that the proposed method outperformed the intensity feature registration approach. The benefits of combining infrared and visible images for the interpretation of infrastructure defects were also reported on previous studies [15,59,60], highlighting the concept that the different targeted defects have enhanced texture and color characteristics registered in visible images, while the thermal data register important temperature differences related to faulty materials or components.…”
Section: Texture-based Segmentation For Improving Multi-modal Analysi...supporting
confidence: 65%
“…A basic CNN architecture includes a convolutional layer, a pooling layer, and a fully connected layer [9,10,12,13].…”
Section: Cnnmentioning
confidence: 99%
“…Ibragimov (2022) conducted a study on detecting distress in the pavement through convolutional neural networks, and Jiang et al (2022) detected and segmented cracks in road pavements through a two-step deep learning approach [21,22]. Chandra et al (2022) studied the seasonal effect to detect complex pavement defects and Chen et al (2022) used thermal images to detect pavement damages [23,24]. Recently, studies on locating damage such as potholes through 3D data are also being conducted [25].…”
Section: Introductionmentioning
confidence: 99%